Efficacy and safety of distinct regimens for individuals with advanced EGFR-mutated non-small-cell lung cancer who progressed on EGFR tyrosine-kinase inhibitors: a systematic review and network meta-analysis - Wengang Zhang; Jian Xiong; Yujie Li; Jing Nie; Wencheng Zhao; Zhiyi Guo; Xinyue Liu; Qianqian Zhang; Xuyang Chen; Li Ye; Zhimin Chen; Hao Wang; et al. (Therapeutic Advances in Medical Oncology)
Background: Targeted therapy with EGFR tyrosine-kinase inhibitors (TKIs) is the preferred first-line treatment for EGFR-mutated advanced non-small-cell lung cancer (NSCLC), but acquired resistance inevitably occurs in almost all responding individuals. Objectives: We aimed to comprehensively review the literature to investigate the efficacy and safety of distinct regimens in the subsequent-line setting, thereby identifying the optimal regimen for these TKI-resistant NSCLC patients. Design: A systematic review and network meta-analysis (NMA) using a Bayesian framework. Data sources and methods: The PubMed, Embase, Cochrane Library databases, and abstracts of ASCO, ESMO, and WCLC were searched from database inception to November 3, 2024, to identify eligible randomized controlled trials (RCTs) that assessed distinct regimens for individuals with advanced EGFR-mutated NSCLC who progressed on TKIs. The outcomes of progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and grade 3 or higher adverse events (⩾3AEs) were compared and ranked in overall patients and various subgroups among eight regimens by NMA and the surface under the cumulative ranking curve, respectively. The protocol is registered with PROSPERO, CRD42024601619. Results: In total, 14 RCTs, involving 3177 participants and 8 treatment regimens (chemotherapy plus ivonescimab (programmed cell death protein 1/vascular endothelial growth factor inhibitor; chemotherapy + ivonescimab (CT + IVO)); CT + amivantamab + lazertinib (CT + AMI + LAZ), CT + immunotherapy + bevacizumab (CT + IO + BEV), CT + AMI, CT + BEV, CT + IO, CT, and IO), were included. Overall, in patients, the most pronounced PFS benefit was observed with the “CT + IVO,” followed by “CT + AMI + LAZ,” “CT + IO + BEV,” and “CT + AMI,” ranked second, third, and fourth, respectively. In terms of OS, the regimen of “CT + AMI” ranked the best, followed by “CT + IVO.” However, the comparisons of OS among different regimens did not reach statistical significance, possibly due to immature data. The results for ORR and DCR were similar to those for OS, with “CT + AMI” topping the rankings, followed by “CT + AMI + LAZ.” In terms of safety, the incidence of ⩾3AEs was highest in “CT + AMI + LAZ,” followed by “CT + AMI.” In subgroup analysis, “CT + IVO” demonstrates stable PFS benefits across clinicopathological characteristics, ranking first in most subgroups. Due to the unavailability of OS subgroup data in most RCTs, many regimens were missing in the OS subgroup analysis. Conclusion: Integrating the results of different clinical outcomes and subgroup analyses, we conclude that “CT + IVO” is the optimal treatment option with an acceptable safety profile for patients with advanced EGFR-mutated NSCLC who have progressed on TKIs. “CT + AMI + LAZ” and “CT + AMI” are alternative subsequent line options as well, with superior efficacy compared to immunotherapy-based or chemotherapy regimens, yet elevated toxicity profiles requiring vigilant management.